Comparative of Rivest-Shamir-Adleman cryptosystem and its four variants using running time and memory consumption analysis - Mandangan, Arif; Asbullah, Muhammad Asyraf; Adnan, Syed Farid Syed; Budiman, Mohammad Andri (Penerbit UTM Press, 2024)
The Rivest-Shamir-Adleman (RSA) algorithm, known for its slow single-precision multiplication (spm) and overall running time, is not commonly employed to encrypt user data directly. As a result, several researchers have developed various RSA-based cryptosystems to enhance the algorithm's performance while maintaining security. This paper presents a comparative analysis of different variants of the RSA cryptosystem, focusing on five specific cryptosystems: RSA, Somsuk-RSA, Modified-RSA (MRSA), Easy Simple Factoring-RSA (ESF-RSA), and Phony-RSA. The methodology involves evaluating the theoretical running time and memory usage through single-precision multiplication (spm) measurements, while the actual running time is estimated using Maple programming. The research has two primary objectives. Firstly, they examined each algorithm of the RSA variants and analysed them according to the proposed methodology. Secondly, to determine which cryptosystem consumes the most time and memory for key generation, encryption, and decryption. The results indicate that ESF-RSA and RSA are the fastest in terms of key generation, ESF-RSA is the quickest for encryption, and Phony-RSA excels in decryption speed. Additionally, ESF-RSA demonstrates the lowest memory usage, whereas MRSA requires the highest memory allocation for all processes.